POVERTY ALLEVIATION OF FARMING COMMUNITY IN HAOR AREA THROUGH FARMING SYSTEMS - Karim, Md. Mahboob; Bhuiya, Md. Sultan Uddin (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
The project entitled âLivelihood Improvement of Farming Community in Haor Area through System Approach (LIFCHASA)â of the Department of Agronomy, Bangladesh Agricultural University; Mymensingh worked in Purbo Tethulia village of Mohanganj Upazila under Netrakona district from April 2010 to June 2013 with the financial assistance from The Bangladesh Agricultural Research Council. Different research activities were done as per plan for different five components. The Crop and Agroforestry Component conducted experiments both in the homestead land and crop land. Under Livestock Component, experiments were conducted on rearing of egg producing hen, duck, fattening of animals, artificial insemination and continuous vaccination programme. In the Fisheries Component, experiments on cage culture in open water emerged as a promising technology. From the result of the soil sample analysis of the research site under Rural Hydrology and Mechanization Component, it was found that additional application of sulphur and zinc fertilizers were unnecessary. From the study under Socioeconomic Component, it was distinctly clear that the efficiency of marginal and small farms was improved in agro economic productivity with the increase of number of farming enterprises intervened irrespective of farm sizes. The marginal and small farmers appeared to be the most efficient performers in the integration and arrangement of farming enterprises. This was followed by landless and medium farms. The gross margin for marginal and small, landless and medium increased by 84%, 89% and 50 %, respectively involving the enterprises like crop and agroforestry, livestock and fisheries. The findings of 25 physical models on integrated farming systems revealed that the agro-economic/bio-economic productivity of all those models increased tremendously in terms of total production, biodiversity, human resource enlightened with knowledge, skill and motivational spirit in modern techniques and technologies.